Difference in higher education pedagogies: gender, emotion and shame. Issue 4 (7th June 2017) - Burke, Penny Jane
ABSTRACT: This paper draws attention to gendered inequalities in relation to pedagogic participation, the politics of difference and the concept of 'shame'. I use the term 'pedagogic participation' to illuminate the relationship between formations of difference, policy concerns to improve 'equity' and higher education participation in and across contested pedagogical spaces. Engaging feminist critiques and analyses of pedagogical practices and 'inclusion', I consider possibilities for creating 'parity of participation' in relation to the social justice struggles of redistribution, recognition, representation and embodied subjectivities. How might students and teachers create spaces for the parity of participation across and among these three inter-related social justice domains and formations of difference in ways that acknowledge the lived and embodied politics of emotion and shame? Through exploring this question, I aim to re/imagine difference as a critical resource for opening up ethical, praxis-based pedagogical spaces and relations.